Alternative delivery of a thermostable inactivated polio vaccine. Issue 17 (21st April 2015) - Kraan, Heleen; Ploemen, Ivo; van de Wijdeven, Gijsbert; Que, Ivo; Löwik, Clemens; Kersten, Gideon; Amorij, Jean-Pierre
Highlights Potential of Bioneedle technology for inactivated polio vaccine (IPV) was evaluated. IPV in Bioneedles is more resistant to elevated temperatures than liquid IPV. Comparable immunogenicity of IPV-Bioneedle and liquid IPV after booster vaccination. Similar kinetics at administration site for Bioneedle compared to liquid injection. LPS-derivate PagL is potent adjuvant for liquid IPV, not for IPV-Bioneedles.